Geração de testes automatizados : uma análise comparativa no processo de garantia de qualidade de software - Coimbra, Waldemar Jr. Dias (2020)
To ensure quality, teams always seek the path that provides the most productivity in the execution of activities, one of which is the automation of tests. Automating tests for certain systems can result in a large number of repeated codes. However, currently there are solutions that can solve the problem of high code repetition, especially the use of code generators, such as JHipster. This generator uses metadata and templates to generate its files, however, it became evident that there is a complexity in the implementation of templates for generating code for this tool. Aiming at an alternative to this model, we sought to implement templates using the fine-grained template approach, in order to compare which template approach demonstrates better encapsulation, allowing for better code reuse. Through the research it was possible to highlight that the fine-grained approach can improve the maintenance of templates for code generation, considering that through this approach it is possible to fragment the responsibilities of templates, thus improving the encapsulation, allowing the best code reuse.